Pengaruh Penggunaan Media Sosial, Motivasi Intrinsik Dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Mahasiswa - Nurhasanah, Vina; Sadiah, Ati; Gumilar, Rendra (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The problem in this study is the low interest of students in entrepreneurship besides that, this study aims to determine the number of people who want to become entrepreneurs so that the economic level in Indonesia increases and becomes an opportunity to create jobs not only rely on jobs because of the high unemployment rate in Indonesia. The purpose of this study was to determine the effect of social media use, intrinsic motivation and entrepreneurial knowledge on entrepreneurial interest. The research method uses a survey with a descriptive design. The population is students of the Economics Education Department of Siliwangi University Class of 2020-2023, totaling 503 students. while the sampling technique used is prabobability sampling type proportionate stratified sampling. So that the total sample taken was 222 students consisting of the number of Class of 2020 as many as 52 people, Class of 2021 as many as 49 people, Class of 2022 as many as 60 people and Class of 2023 as many as 61 people. Data collection techniques using questionnaires, data analysis techniques using classical assumption tests, linear regression tests and hypothesis testing. The results showed that the use of social media has a significant effect on the entrepreneurial interest of economic education students in the Class of 2020 - 2023 with a significance value smaller than 5% (0.000 <0.05), also with intrinsic motivation has a significant effect on entrepreneurial interest in economic education students in the Class of 2020 - 2023 with a significance value smaller than 5% (0.000 <0.05), Likewise with entrepreneurial knowledge that has on entrepreneurial interest in economic education students class of 2020 - 2023 with a significance value smaller than 5% (0.001 <0.05), the use of social media, intrinsic motivation and entrepreneurial knowledge has a positive influence significance on entrepreneurial interest in economic education students Class of 2020 - 2023, with a significance value smaller than 5% (0.000 <0.05).